Effect of a probiotic formula on gastrointestinal health, immune responses and metabolic health in adults with functional constipation or functional diarrhea - Zheng, Yanyi; Xu, Leiming; Zhang, Silu; Liu, Yanwen; Ni, Jiayi; Xiao, Guoxun (Frontiers in Nutrition, 2023)
Objective: Our aim was to determine the efficacy of four-week probiotic supplementation on gastrointestinal health. The secondary objectives were to assess probiotic effects on immune reaction, as well as weight control and metabolic health. Methods: We conducted two randomized sub-trials, respectively, among subjects who were diagnosed with functional constipation (FC) or functional diarrhea (FDr) according to the Rome IV criteria. In each sub-trial, 70 eligible Chinese adults were randomized to receive a multi-strain probiotic combination or a placebo. Gastrointestinal symptoms, defecation habits, stool characteristics, blood and fecal biochemistry markers, anthropometrics measures, stress-associated responses, and intestinal flora changes were assessed at baseline and after probiotics intervention. Results: Four weeks of probiotic supplementation reduced overall gastrointestinal symptoms scores in FC participants (p<0.0001). Their mean weekly stool frequency increased from 3.3 times to 6.2 times; immune response and inflammation markers improved with increases in serum IgA, IFN-γ and fecal sIgA, and decrease in hsCRP; most components of lipid profile were significantly ameliorated, with increases in HDL and reductions in TC and TG; body weight, body mass index and basal metabolic rate decreased following probiotics consumption. For FDr participants, probiotics consumption markedly reduced overall gastrointestinal symptom scores (p<0.0001); decreased stool frequency by 3 times per week; increased IgA, IFN-γ, sIgA concentrations, while lowered hsCRP and IL-4 levels. Both FC and FDr participants had improvement in the scores of defecation habits, anxiety or depression, and perceived stress. Probiotics supplementation promoted the production of all three major short-chain fatty acids. No changes were observed in LDL, IgG, IgM, IL-8, IL-10 and motilin. Conclusion: Supplementation with the probiotic formula over a four-week period could help relieving gastrointestinal symptoms, improving satisfaction with defecation habits, emotional state and immune response, and ameliorating dysbacteriosis in participants with FC or FDr. It also had beneficial effects on lipid metabolism and weight control for FC participants.